A U-shaped association between serum betaine and incident risk of first ischemic stroke in hypertensive patients. Issue 8 (August 2020) - Xie, Liling; Zhao, Bo-xin; Luo, Jiajun; Li, Youbao; Zhu, Fengxin; Li, Guo-feng; He, Mingli; Wang, Binyan; Zhang, Hao; Cai, Yefeng; Huo, Yong; Wang, Xiaobin; et al.
Summary: Background & aims: Betaine (a micronutrient) has important biological functions (e.g., preventing premature apoptosis and serving as a methyl donor). We investigated the association between baseline serum betaine and the incident risk of first stroke in hypertensive patients. Methods: We conducted a nested case–control study, including 622 patients with first stroke (including 502 ischemic stroke, 118 hemorrhagic stroke and 2 uncertain type of stroke) and 622 matched controls from the China Stroke Primary Prevention Trial (CSPPT). The study was conducted from May 2008 to August 2013. The study outcomes included first stroke and its subtypes: first ischemic and hemorrhagic stroke. Results: There was a U-shaped association between baseline serum betaine and the risk of first ischemic stroke. The risk of first ischemic stroke decreased with the increment of betaine (per 10 μmol/L increase: OR, 0.87; 95%CI: 0.77–0.99) in patients with betaine <77.7 μmol/L, while the risk of first ischemic stroke increased with the betaine increment (OR, 1.17; 95%CI: 1.01–1.36) in patients with betaine ≥77.7 μmol/L. However, there was no significant association between serum betaine and risk of first hemorrhagic stroke (per 10 μmol/L increase: OR, 0.98; 95%CI: 0.82–1.17). Conclusions: There was a U-shaped association between baseline betaine levels and the risk of first ischemic stroke in hypertensive patients, with a turning point at about 77.7 μmol/L. Clinical trial registration-URL: http://www.clinicaltrials.gov . Unique identifier: NCT00794885.